THE IMPACT OF THE ORGANIZATIONAL CULTURE TRAITS ON TASK PERFORMANCE THROUGH PERSONALITY TRAITS AMONG THE EMPLOYEES OF THE SEMI-GOVERNMENTAL ORGANISATIONS IN SAUDI ARABIA - Awad Algawazi; Mas Bambang; Ebi Sahrin (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to investigate the mediating role of personality traits (openness to experience) between organizational culture traits (involvement culture) and task performance among the employees of semi-governmental organizations in Saudi Arabia. In this regard, an online questionnaire was distributed to the low and medium level employees of these organizations; namely Aramco, General Commission of Audio-Visual Media, Saudi Electricity Company and Saudi Telecom Company. 342 usable responses out of 368 were examined in the research. The findings of this study showed that personality traits partially play a mediating role between organizational culture and task performance. The findings show that openness to experience is not influential antecedents to task performance within the organizational culture. Furthermore, the findings of the study have important implications for future practice. It provides policy direction and practical implications to the organizational culture, managers of organizations, and researchers. Future researchers should focus on organizational change and quantitative studies to produce a comprehensive understanding of job performance. Future research should also focus on other mediating or moderating factors effects on Task performance.